1999
DOI: 10.1073/pnas.96.24.14073
|View full text |Cite
|
Sign up to set email alerts
|

Global GacA-steered control of cyanide and exoprotease production in Pseudomonas fluorescens involves specific ribosome binding sites

Abstract: The conserved two-component regulatory system GacS͞GacA determines the expression of extracellular products and virulence factors in a variety of Gram-negative bacteria. In the biocontrol strain CHA0 of Pseudomonas fluorescens, the response regulator GacA is essential for the synthesis of extracellular protease (AprA) and secondary metabolites including hydrogen cyanide. GacA was found to exert its control on the hydrogen cyanide biosynthetic genes (hcnABC) and on the aprA gene indirectly via a posttranscripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
257
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(267 citation statements)
references
References 37 publications
9
257
0
1
Order By: Relevance
“…The role of PsrA and RpoS in phenazine synthesis has so far not been studied in strain 30-84. The following hypothesis would reconcile the results in both strains: GacS/GacA could regulate phzI at the transcriptional level and phzR at the post-transcriptional level, since it was shown that GacA acts at both levels (Blumer et al, 1999;Pessi & Haas, 2001). In our gacS mutant, the presence of constitutively expressed phzR would result in an excess of PhzR mRNA that would overcome negative posttranscriptional regulation.…”
Section: Discussionmentioning
confidence: 90%
“…The role of PsrA and RpoS in phenazine synthesis has so far not been studied in strain 30-84. The following hypothesis would reconcile the results in both strains: GacS/GacA could regulate phzI at the transcriptional level and phzR at the post-transcriptional level, since it was shown that GacA acts at both levels (Blumer et al, 1999;Pessi & Haas, 2001). In our gacS mutant, the presence of constitutively expressed phzR would result in an excess of PhzR mRNA that would overcome negative posttranscriptional regulation.…”
Section: Discussionmentioning
confidence: 90%
“…First, in a variety of other gram-negative bacteria, homologues of LetA/LetS activate gene expression indirectly by counteracting the effects of CsrA, a repressor of translation (8,12,20,21). Secondly, in PE-phase L. pneumophila, LetA/LetS and RpoS may mediate the decay of letE RNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting 635-bp upstream and 955-bp downstream fragments were cleaved with HindIII ϩ BamHI, and BamHI ϩ EcoRI, respectively, and inserted into the suicide plasmid pME3087 (14) cut with HindIII ϩ EcoRI. The resulting plasmid pME7315 was introduced into strains CHA0, CHA207, CHA805, CHA825, CHA826, and CHA827 (13,14,18) to generate, via homologous recombination, the corresponding mutants CHA1141 (⌬rsmX), CHA1142 (⌬rsmX, hcnAЈ-ЈlacZ), CHA1143 (⌬rsmX, aprAЈ-ЈlacZ), CHA1144 (⌬rsmX ⌬rsmY ⌬rsmZ), CHA1145 (⌬rsmX ⌬rsmY ⌬rsmZ, hcnAЈ-ЈlacZ), and CHA1146 (⌬rsmX ⌬rsmY ⌬rsmZ, aprAЈ-ЈlacZ). An rsmX-lacZ fusion was constructed by PCR amplification of the 312-bp rsmX promoter region with primers PROF and PROR1 (Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…In E. coli, CsrA regulates the utilization of carbon sources, glycogen synthesis, biofilm formation, and motility (7)(8)(9)(10)(11), whereas in Erwinia carotovora, the CsrA homolog RsmA (repressor of secondary metabolism) controls the expression of extracellular enzymes and type III secretion (12). The similar RsmA and RsmE proteins of the plant-beneficial root-colonizing biocontrol strain CHA0 of Pseudomonas fluorescens negatively regulate the synthesis of extracellular antifungal secondary metabolites (13)(14)(15). Small noncoding RNAs, such as CsrB and CsrC of E. coli (8,16), RsmB of E. carotovora (17), or RsmZ and RsmY of P. fluorescens (14,18), bind multiple CsrA͞RsmA molecules with high affinity and thereby allow translation of mRNAs, which are repressed by CsrA or RsmA.…”
mentioning
confidence: 99%